Comparison of printed and electronic bara (booklet for prevention of hypertension in pregnancy) on knowledge, attitudes and actions for prevention of hypertension in pregnancy - Zuraidah Zuraidah; Nadi Aprilyadi; Wiwin Martiningsih; Mujito Mujito; Indah Dewi Ridawati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The maternal mortality rate in Indonesia is still considered high, at 305 per 100,000 live births. Hypertension in pregnancy is the second largest cause of maternal death in Indonesia. In 2018, two mothers died due to hypertension in pregnancy at the Simpang Periuk Health Center, Lubuklinggau City. One of the causes of hypertension in pregnancy that leads to death is the lack of information obtained by pregnant women. Health promotion through booklet media is a solution to increase the knowledge, attitudes and actions of pregnant women regarding the prevention of hypertension in pregnancy. BARA (Small Book of Prevention of Hypertension in Pregnancy) is a small book containing specific knowledge about successful strategies for preventing hypertension in pregnancy. Providing knowledge about the prevention of hypertension in pregnancy through booklets distributed to pregnant women has never been done at the Simpang Periuk Health Center. Purpose: To compare the average score, difference, and percentage change in knowledge, attitude, and action regarding hypertension prevention before and after receiving BARA in pregnant women. Method: Quantitative research using quasi-experimental design with control group. The sample used was 60 pregnant women obtained by Accidental Sampling formula. The study was conducted at Simpang Periuk Health Center, Lubuklinggau City. This location was chosen because based on initial data, the researcher concluded that many pregnant women at Simpang Periuk Health Center still have low levels of knowledge, attitudes, and actions regarding hypertension in pregnancy. Group 1 was given a printed BARA book, while Group 2 was included in the WhatsApp group where the electronic BARA book was distributed. Participants read the booklet and were encouraged to ask questions if they found something unclear. Results: Almost all participants were aged between 20-35 years (90%) with an average age and standard deviation of 27.21 and 4.498. The majority of participants had a high school education (48.3%) and most participants were housewives (52%). The average results of hypertension prevention actions in pregnancy in participants who used printed and electronic books increased significantly. Preventive actions in the group using printed booklets increased from 16.33 to 19.20, while in the e-booklet group increased from 16.07 to 19.13. The results of the Wilcoxon statistical test showed a p-value of 0.000 (p <0.05). This indicates a significant difference in actions before and after health promotion. Conclusion: There is a significant difference in the level of knowledge, attitudes, and actions regarding hypertension in pregnancy before and after health education using both printed and electronic booklets. There was a significant increase in knowledge, attitudes, and actions to prevent hypertension in pregnancy (p<0.000) in both groups. The greatest increase occurred in the group given the e-booklet.